Hospitalization costs for heart failure in people with type 2 diabetes: Cost-effectiveness of its prevention measured by a simulated preventive treatment - Caporale, Joaquín Enzo (2011)
Objectives: To estimate the cost-consequence of interventions to prevent hospitalizations for heart failure (HF) in people with type 2 diabetes. Methods: In HF events (63) from type 2 diabetes-related hospitalizations (N = 462) recorded in an Argentine hospital (March 2004April 2005), we verified 1) the presence of one metabolic HF predictor (glycosylated hemoglobin [HbA1c] value) before hospitalization; and 2) in a simulation model, the resources needed for its prevention controlling such predictor during 6 months before and after the event. Sensitivity analysis of HF risk reduction, hospitalization cost, and cost of different treatments to achieve HbA1c 7% or less was performed with a Monte Carlo simulation (10,000 iterations). Results: HF represented 14% of hospitalizations, with a 44% rehospitalization rate for the same cause. Due to the total estimated cost for an HF hospitalization event was $437.31, the prevention attained using our simulated treatment was $2326.51. The number needed to treat to prevent an HF event under any of the proposed alternatives to reduce HbA1c would be 3.57 (95% confidence interval 2.0016.67). The additional cost of the simulated treatment versus the real one oscillates between $6423.91 and $8455.68. Conclusions: HbA1c control to reduce the number of HF events would be economically beneficial for health care payers.